Effect of Porphyromonas gingivalis on epithelial cell MMP-9 type IV collagenase production. - Fravalo, P (1996)
Porphyromonas gingivalis is reportedly capable of stimulating the expression of host cell matrix metalloproteinases (MMP), contributing to tissue destruction. However, the impact of this bacterium on specific molecules remains to be determined. In this study, we evaluate the effect of P. gingivalis on regulation of MMP-9 expression in human gingival epithelial cells (HGEC). Various inocula of P. gingivalis were added to cultures of HGEC. The effects of live bacteria, heat-killed bacteria, and outer membrane extract were analyzed. MMP-9 secretion by HGEC was evaluated by enzyme-linked immunosorbent assay. For inocula smaller than one bacterium per cell, the quantity of MMP-9 secreted by HGEC was increased in comparison to control conditions. For inocula from 2.5 to 250 bacteria per cell, an inhibition of MMP-9 secretion in a dose-response fashion was observed, with a maximum reduction (ranging from 80 to 95% in five experiments) at 50 bacteria per cell. Gelatin zymograms confirmed the decrease in MMP-9 secretion. A band of 83 kDa, corresponding to activated enzyme, was present for inocula of 0.5 to 50 bacteria. Inhibition took place without any alteration of epithelial cell viability. Heat-killed bacteria and outer membrane extract also provoked proenzyme activation but did not inhibit MMP-9 secretion. These results demonstrate a direct effect of P. gingivalis on HGEC, suggesting a specific action on the collagen renewal process at the interface between the epithelium and connective tissue.